2022
DOI: 10.3390/biom12101507
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in the Membrane Transport of Phenylethylamine Derivatives by Human Monoamine Transporters and Organic Cation Transporters 1, 2, and 3

Abstract: Stereoselectivity is well known and very pronounced in drug metabolism and receptor binding. However, much less is known about stereoselectivity in drug membrane transport. Here, we characterized the stereoselective cell uptake of chiral phenylethylamine derivatives by human monoamine transporters (NET, DAT, and SERT) and organic cation transporters (OCT1, OCT2, and OCT3). Stereoselectivity differed extensively between closely related transporters. High-affinity monoamine transporters (MATs) showed up to 2.4-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The trend of higher stereoselectivity in OCT2 and −3 inhibition compared to OCT1 aligns with previous studies on stereoselective OCT transport demonstrating that OCT2 and OCT3 act more stereoselectively than OCT1. , Recent structural data based on cryogenic electron microscopy (cryo-EM) have confirmed a fundamentally similar substrate binding cavities of all three OCTs. , Nevertheless, there were also more than 10 amino acids that differ between the three transporters and may therefore be responsible for substrate- and stereoselectivity. The long-known polyspecificity of OCTs was reflected for OCT1 by an orthosteric and opportunistic ligand binding site .…”
Section: Discussionsupporting
confidence: 87%
“…The trend of higher stereoselectivity in OCT2 and −3 inhibition compared to OCT1 aligns with previous studies on stereoselective OCT transport demonstrating that OCT2 and OCT3 act more stereoselectively than OCT1. , Recent structural data based on cryogenic electron microscopy (cryo-EM) have confirmed a fundamentally similar substrate binding cavities of all three OCTs. , Nevertheless, there were also more than 10 amino acids that differ between the three transporters and may therefore be responsible for substrate- and stereoselectivity. The long-known polyspecificity of OCTs was reflected for OCT1 by an orthosteric and opportunistic ligand binding site .…”
Section: Discussionsupporting
confidence: 87%
“…Generally, their stereoselectivity is much higher than that of OCT1, which is in accordance with previous reports. 26,28 With none of the substrates, there was absolutely zero transport for one of the enantiomers and a relevant transport for the other enantiomer, but as illustrated in Figures 2 and 3, particularly terbutaline and zolmitriptan transport by OCT3 was highly enantioselective.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 94%
“…Overview of stereoselectivity of SLC22 organic cation transporters. V max ratios are shown for all OCT substrates in ascending order where data on stereoselective transport kinetics were available. , Data are presented as the v max ratio of the higher transported enantiomer over the other. Substrates investigated in this study are highlighted by dark filling, whereas data taken from the literature are indicated by lighter fillings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations